Evaluasi Penerapan Kurikulum Muatan Lokal Menggunakan Model Evaluasi CIPP - Hendri; Supratman Zakir; Darul Ilmi (Kariman: Jurnal Pendidikan Keislaman, 2024)
Indonesia has a diversity of customs, languages, arts, crafts and regional skills. In the current era of globalisation in Indonesia, information flowing from one place to another cannot be blocked. Therefore, character and culture-based learning such as PKBAM and PUPB are needed. This study aims to determine the implementation of the local content curriculum of PKBAM and PUPB in Bukittinggi City. This research uses the CIPP (Context, Input, Process, Product) evaluation model. The research subjects were principals and teachers. The results showed context evaluation that the PKBAM and PUPB programmes were implemented in all schools at the SD/MI/SDLB and SMP/MTs/SMPLB levels in Bukittinggi City, consisting of 80 schools. Input evaluation that the ESCAM and PUPB programmes are implemented by students who are taught by guest teachers who are appointed directly specifically to teach ESCAM and PUPB materials, teaching materials are prepared in accordance with learning objectives and workshops are held to prepare and revise teaching materials by teachers, ESCAM curriculum is related to minangkabau culture and customs, while for PUPB consists of fiqh, aqidah akhlak, Arabic language, and sirah nabawiyyah, related to facilities and infrastructure for each school is considered appropriate. Evaluation of the learning process that the lesson hours for elementary / MI / SDLB classes I, II, III, are carried out 1 JP with separate methods, for classes IV, V, VI are carried out 1 JP with separate methods. Evaluation of the product that students in Bukittinggi city have begun to see changes in terms of attitude and evaluation of the PKBAM and PUPB programmes is considered to have run well and quite effectively